1997
DOI: 10.1183/09031936.97.10091975
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of effective ventilation during nasal intermittent positive pressure ventilation

Abstract: Our aim was to verify in healthy subjects submitted to nasal intermittent positive pressure ventilation (nIPPV) with a volumetric ventilator on controlled mode, whether changes in ventilator settings (delivered tidal volume (VT), respiratory frequency (fR) and inspiratory flow (V 'I)) could influence effective minute ventilation (V 'E), thus allowing identification of the settings resulting in the highest V 'E during nIPPV. We then compared these experimentally obtained "best" settings to those obtained retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…This can be explained by the need, in these patients, to modify the Pa,CO 2 to a greater extent, which could cause ''resistance'' to the ventilation, as has been described previously [24]. For stable patients, there was a significant correlation between the presence of abnormalities in ResLink TM data and a reduced efficacy of NIV, particularly in terms of Pa,O 2 , pH and HCO 3 -.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This can be explained by the need, in these patients, to modify the Pa,CO 2 to a greater extent, which could cause ''resistance'' to the ventilation, as has been described previously [24]. For stable patients, there was a significant correlation between the presence of abnormalities in ResLink TM data and a reduced efficacy of NIV, particularly in terms of Pa,O 2 , pH and HCO 3 -.…”
Section: Discussionmentioning
confidence: 74%
“…There are several possible explanations for this. One is that greater modification of Pa,CO 2 as a result of more hermetic ventilation could promote the occurrence of glottal closure episodes [24]. Another is that the use of FM predominantly induces mouth breathing, which may promote significant narrowing of the retropalatal distance predisposing to oropharyngeal obstruction [34].…”
Section: Discussionmentioning
confidence: 99%
“…These choices were made in order to simplify data presentation, and to represent the range of settings commonly encountered clinically [10]. The two leaks were selected to range below and above those measured in a previous clinical study [3], and ideal settings were used for NPPV based on recommendations in the literature [8,9]. Third, the effects of leak on ventilator triggering or cycling during spontaneous breathing were not tested, so the observations are most relevant to situations where controlled breathing predominates, such as in neuromuscular patients during sleep [3].…”
Section: Discussionmentioning
confidence: 99%
“…min -1 in all of the experiments to reflect commonly recommended breathing rates for noninvasive ventilation [8,9]. IPAP/EPAP settings were 18 and 5 cmH 2 O respectively for the BiPAP (in both T and S/T modes), 335, and Quantum ventilators.…”
Section: Experimental Settingsmentioning
confidence: 99%
“…The glottis is an essential structure in nIPPV, since, in response to assisted ventilation with positive pressures, it can substantially narrow and even, completely close, thus increasing the risks of leaks, decreasing the usefulness of nIPPV and impairing sleep quality [12,13]. It has been shown that changing the delivered tidal volume, inspiratory flow and ventilatory frequency, or the positive inspiratory pressure (as well as manipulating the ventilatory mode), can influence the glottic response and improve the ventilation effectively reaching the lungs during sleep [14,15]. TESCHLER et al [10] attributed the decrease in ventilation and the poor sleep quality to the presence of leaks (i.e.…”
mentioning
confidence: 99%